Ca(2+) permeability of nicotinic acetylcholine receptors in rat hippocampal CA1 interneurones - Fayuk, Dmitriy (Blackwell Science Inc, 2005)
Neuronal nicotinic acetylcholine receptors (nAChRs) are widely expressed in the brain where they are involved in a variety of physiological processes, including cognition and development. The nAChRs are ligand-gated cationic channels, and different subtypes are known to be differentially permeable to Ca(2+); the α7-containing nAChRs are generally considered to be the most permeable. Ca(2+) can activate and regulate a variety of signal transduction cascades, and the influx of Ca(2+) through these receptors may have implications for synaptic plasticity. To determine the Ca(2+) permeability of the nAChRs in rat hippocampal interneurones in the slice, which contain diverse subtypes of α7- and non-α7-containing nAChRs, we combined patch-clamp electrophysiology recordings with conventional fura-2 fluorescence imaging techniques. We estimated the relative Ca(2+) permeability of the channels by determining the ratio of the increase in [Ca(2+)](i) level (Δ[Ca(2+)](i)) in the soma to the integrated transmembrane current (charge, Q) induced by the activation of the nAChRs, and compared this ratio to the highly Ca(2+) permeable NMDA subtype of glutamate receptor channel. In all cells tested, the Δ[Ca(2+)](i)/Q ratio was significantly larger (i.e. more than twice as big) for responses activated by NMDA than for α7-containing nAChRs in interneurones; the activation of the non-α7 nAChRs did not produce any significant increase in [Ca(2+)](i). Interestingly, the Ca(2+) permeability of native α7 nAChRs in PC12 cells was significantly larger than in hippocampal interneurones, and not significantly different from NMDA receptors. Therefore, the α7-containing nAChRs in rat hippocampal interneurones are significantly less permeable to Ca(2+) than not only NMDA receptors but also α7 nAChRs in PC12 cells.